ІНТЕГРАЦІЯ ГРУПОВИХ ТА ІНДИВІДУАЛЬНИХ ФОРМ ВПЛИВУ НА ПІДЛІТКІВ У ПРОЦЕСІ ПЕДАГОГІЧНОЇ ПРОФІЛАКТИКИ ДЕВІАНТНОЇ ПОВЕДІНКИ - Самойлов, Анатолій (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті проаналізовано напрями профілактичної роботи з девіантними підлітками, які створюють можливість для інтеграції групових та індивідуальних форм виховного впливу на особистість важковиховуваного. Розглянуто особливості діяльності учнівського самоврядування, зокрема його функції, пов’язані з впливом на педагогічно занедбаних підлітків. Описані ступені моральної готовності колективу, що визначає ефективність виховного впливу підліткового колективу на спрямованість особистості важковиховуваного. Відповідно до етапів профілактики охарактеризовано різновиди прийомів індивідуального підходу: прямий, непрямий і комбінований. В статье проанализированы направления профилактической работы с девиантными подростками, которые создают возможность для интеграции групповых и индивидуальных форм воспитательного воздействия на личность трудновоспитуемого. Рассмотрены особенности деятельности ученического самоуправления, в частности его функции, связанные с воздействием на педагогически запущенных подростков. Описанные степени моральной готовности коллектива, определяет эффективность воспитательного воздействия подросткового коллектива направленность личности трудновоспитуемого. Согласно этапов профилактики охаракте-ризованы разновидности приемов индивидуального подхода: прямой, косвенный и комбинированный. The paper analyzes the direction of the preventive work with deviant teenagers that create the opportunity for the integration of group and individual forms of educational influence on the personality of difficult and pedagogical conditions of their influence in the process of teaching the prevention of the deviant behavior. The features of the activities of student self-government, in particular its functions related to exposure to pedagogically neglected teenagers. Describe the degree of moral readiness team, determines the efficiency of educational influence adolescent collective orientation of the person maladjusted. The analysis of the specific use methods of the educational influence, provides an individual approach to the prevention of deviant behavior and direction of the effective implementation of a collective approach to the educational and preventive work. According to the steps described species prevention practices individual approach: direct, indirect and combined. Details covered pedagogical conditions of use of methods of separation, «vaccination», reorientation; receptions restoration and incentive, brake, auxiliary. The attention was focused on the aspects of a pedagogical management, aimed at the formation of the moral and legal traditions in the team, ensuring the integration of business and personal relationships.